"No One Cares, Apostolate": What Social Cheating Reveals. (November 2014) - Thompson, Kathryn
This piece examines the relationship between cheating, play, and work on the social news site Reddit.com. Using cheating as a point of rupture that reveals explicit and implicit game rules as well as ideological parameters of the game itself, I explore the humorous community backlash to the perceived "social cheating" of a prolific user (Apostolate). The backlash seemed to indicate that Apostolate was working excessively at the supposed "play" of Reddit, yet individual users put significant work into creating their playful chastisements, complicating a widespread community understanding of Reddit as "not work." Thus, I argue that just as cheating cannot be considered the "other" of play, neither can work be considered the other of Reddit. Both are points of rupture which reveal the underlying mechanisms of the systems they are purported to "ruin."